Hospitalizations With Observation Services and the Medicare Part A Complex Appeals Process at Three Academic Medical Centers. Issue 4 (1st April 2017) - Sheehy, Ann M.; Engel, Jeannine Z.; Locke, Charles F.S.; Weissburg, Daniel J.; Eldridge, Kevin; Caponi, Bartho; Deutschendorf, Amy
Abstract : Hospitalists and other providers must classify hospitalized patients as inpatient or outpatient, the latter of which includes all observation stays. These orders direct hospital billing and payment, as well as patient out‐of‐pocket expenses. The Centers for Medicare & Medicaid Services (CMS) audits hospital billing for Medicare beneficiaries, historically through the Recovery Audit program. A recent U.S. Government Accountability Office (GAO) report identified problems in the hospital appeals process of Recovery Audit program audits to which CMS proposed reforms. In the context of the GAO report and CMS's proposed improvements, we conducted a study to describe the time course and process of complex Medicare Part A audits and appeals reaching Level 3 of the 5‐level appeals process as of May 1, 2016 at 3 academic medical centers. Of 219 appeals reaching Level 3, 135 had a decision—96 (71.1%) successful for the hospitals. Mean total time since date of service was 1663.3 days, which includes mean days between date of service and audit (560.4) and total days in appeals (891.3). Government contractors were responsible for 70.7% of total appeals time. Overall, government contractors and judges met legislative timeliness deadlines less than half the time (47.7%), with declining compliance at successive levels (discussion, 92.5%; Level 1, 85.4%; Level 2, 38.8%; Level 3, 0%). Most Level 1 and Level 2 decision letters (95.2%) cited time‐based (24‐hour) criteria for determining inpatient status, despite 70.3% of denied appeals meeting the 24‐hour benchmark. These findings suggest that the Medicare appeals system merits process improvement beyond current proposed reforms.